United in earnest: first pilot sites for increased surgical capacity for rheumatic heart disease announced by cardiac surgery intersociety alliance. (8th April 2021) - Enumah, Zachary Obinna; Bolman, Ralph Morton; Zilla, Peter; Boateng, Percy; Wilson, Barry; Kumar, A. Sampath; Chotivatanapong, Taweesak; Beyersdorf, Friedhelm; Pomar, Jose; Sliwa, Karen; Eiselé, Jean-Luc; Dearani, Joseph; et al.
Abstract: : OBJECTIVES: Rheumatic heart disease (RHD) affects >33 000 000 individuals, mostly from low- and middle-income countries. The Cape Town Declaration on Access to Cardiac Surgery in the Developing World was published in August 2018, signalling the commitment of the global cardiac surgery and cardiology communities to improving care for patients with RHD. METHODS: As the Cape Town Declaration formed the basis for which the Cardiac Surgery Intersociety Alliance (CSIA) was formed, the purpose of this article is to describe the history of the CSIA, its formation, ongoing activities and future directions, including the announcement of selected pilot sites. RESULTS: The CSIA is an international alliance consisting of representatives from major cardiothoracic surgical societies and the World Heart Federation. Activities have included meetings at annual conferences, exhibit hall participation for advertisement and recruitment and publication of selection criteria for cardiac surgery centres to apply for CSIA support. Criteria focused on local operating capacity, local championing, governmental and facility support, appropriate identification of a specific gap in care and desire to engage in future research. Eleven applications were received for which 3 finalist sites were selected and site visits conducted. The 2 selected sites were Hospital Central Maputo (Mozambique) and King Faisal Hospital Kigali (Rwanda). CONCLUSIONS: Substantial progress has been made since the passing of the Cape Town Declaration and the formation of the CSIA, but ongoing efforts with collaboration of all committed parties—cardiac surgery, cardiology, industry and government—will be necessary to improve access to life-saving cardiac surgery for patients with RHD.